The Model of Law Education to Achieve Progressive Law Enforcement - Sudiyana, Sudiyana (Pandecta Research Law Journal, 2017)
Pendidikan hukum di indonesia cenderung menghasilkan lulusan yang berpikiran positivistik—yang mendorong para penegak hukum berpikir dan bertindak dengan cara legalitas hukum. Selain itu, hakim akan menjadi corong dari peraturan perung-undangan, sehingga mereka tidak bisa memenuhi rasa keadilan masyarakat. Penelitian ini akan menganalisis aturan hukum terkait dengan pendidikan hukum di masyarakat. Hasil penelitian ini menunjukkan bahwa sistem hukum terkait dengan pendidikan hukum di masyarakat masih bernuansa positivisme yang berkesan represif dan tidak responsif. Kondisi ini berpengaruh terhadap corak penegakan hukum yang bersifat legal positivistik. Secara ideal ke depan pendidikan hukum mengintegrasikan pendekatan sosiologis dan prinsip-prinsip keadilan, sehingga penegak hukum yang dihasilkan dari pendidikan hukum menjadi berorientasi kepada keadilan subtantif.The legal education in Indonesia tends to produce graduates who believe in legal positivism that encourages law enforcers to think and act in any legal formalistic way. In addition it places judges as the mouthpiece of the law who cannot express to make decisions that satisfy a sense of social justice and substantive justice. This article is based on the socio-juridical approach by underlying the analysis of the law and regulations which are related to the application of legal education in the community. The legal education is oriented to legal positivism that results in law enforcement with the understanding of law based on the abstract values, not on the values that live and thrive in society, so that the understanding of the law in a legal sense is more repressive, and not responsive. Law is understood as infunctional and unpragmatic thing, therefore understanding of law is the law that merely protects the elite group of citizens, in such a way that equality before the law and the rule of law don’t work. Legal education in the future should be based on the sociological aspects of prioritizing the principles of social justice and the benefits for the community, instead of legal certainty only. Legal education will produce a responsive law enforcement that put substantive fairness and social justice as a legal purpose.